(NwULKANY kARADAGA (B/s - (NdOWGALX(B, (N`RIJ mIHAJLOWI^s; (NrADZIWIL(B, (Nw(B.(Nq(B.s; (NtOKOWENKO(B, (Nw(B.(Ns(B.s; (NnAUMENKO(B, (NwALENTIN wLADIMIROWI^s ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 102-103 (78 (NNAZW(B.)s
(Nan ussr(B, (NiN(B-(NT GEOL(B. (NNAUKs
Keywords: (NwULKANYs; (NkARADAGs